IMPLEMENTATION OF THE PROJECT BASED LEARNING APPROACH IN LEARNING IN ELEMENTARY SCHOOLS - Gebby (Teaching and General Education Studies, 2026)
To facilitate active learning in elementary schools, it is necessary to design and organize learning effectively for the learners. When it is still teacher-centered in many classroom processes, students have lesser interest in the learning process. Therefore, to enhance student participation in learning activity, a suitable learning approach must be developed. One of the methods that could be used is Project Based Learning (PjBL). This study seeks to review the use of Project Based Learning in the elementary education system. The method used in this study is a literature review by analyzing various sources such as books and relevant scientific journal articles. Therefore, applying Project Based Learning in the study results shows that we may be able to develop more involvement and engagement of the students in the learning process, enhance their learning motivation, and encourage them to learn new concepts as well. In addition, this learning mode also serves in enhancing learners’ critical thinking skills, creativity, communication skills, and collaboration skills. Students are closely linked to problem-solving, finding out about a topic through project activities, solving the problems, and product design. Hence, Project Based Learning can be applied as an alternative learning model as a means of enhancing the quality of learning in elementary schools.